2019
DOI: 10.3389/fncel.2019.00131
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Intensity-Dependent Synaptic Inhibition Underlies the Generation of Non-monotonic Neurons in the Mouse Inferior Colliculus

Abstract: Intensity and frequency are the two main properties of sound. The non-monotonic neurons in the auditory system are thought to represent sound intensity. The central nucleus of the inferior colliculus (ICC), as an important information integration nucleus of the auditory system, is also involved in the processing of intensity encoding. Although previous researchers have hinted at the importance of inhibitory effects on the formation of non-monotonic neurons, the specific underlying synaptic mechanisms in the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…Short latencies suggested ascending pathways of excitation and inhibition from the lower auditory nuclei (Ono & Oliver, 2014) because longer latencies were attributed to the increased number of synapses in a pathway (Phillips & Hall, 1990; Walmsley et al., 1998). Consistent with our previous work (Liu et al., 2019), no obvious difference was demonstrated between the latencies of EPSCs and IPSCs. In addition, the range of latencies among those IC neurons suggested that both monosynaptic and polysynaptic pathways were activated (Mauger et al., 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Short latencies suggested ascending pathways of excitation and inhibition from the lower auditory nuclei (Ono & Oliver, 2014) because longer latencies were attributed to the increased number of synapses in a pathway (Phillips & Hall, 1990; Walmsley et al., 1998). Consistent with our previous work (Liu et al., 2019), no obvious difference was demonstrated between the latencies of EPSCs and IPSCs. In addition, the range of latencies among those IC neurons suggested that both monosynaptic and polysynaptic pathways were activated (Mauger et al., 2010).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the range of latencies among those IC neurons suggested that both monosynaptic and polysynaptic pathways were activated (Mauger et al., 2010). It is important to note that the CF of a neuron was typically obtained according to the TRF of the contralateral EPSCs because the TRFs of contralateral and ipsilateral stimulation displayed the same CF (Xiong et al., 2013) and similar phenomena were also noted for excitatory and inhibitory TRFs (Liu et al., 2019; Wei et al., 2018). In this study, recordings were performed in anesthetized mice due to technical demands of whole‐cell recordings and blockage of the AN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The surgical procedures used for mouse electrophysiological recordings were similar to those methods that we previously reported ( Wei et al, 2018 ; Liu et al, 2019 ; Wang et al, 2019 ; Wu et al, 2021 ). Mice were anaesthetized with pentobarbital (60–80 mg/kg, i. p., Sigma, United States) and atropine (0.25 mg/kg, s. c., Nandao, China).…”
Section: Methodsmentioning
confidence: 99%
“…A 700B amplifier (Axon, United States) was used to take our electrophysiological recordings. To perform in vivo loose-patch recordings, the micropipette containing artificial cerebrospinal fluid (ACSF; in mM: 124 NaCl, 2.5 KCl, 25 NaHCO 3 , two CaCl 2 , one MgCl 2 , 1.23 NaH 2 PO 4 , 20 glucose, pH = 7.28) and 0.5% biocytin was attached to the neuron with a loose seal (0.2–1 MΩ) ( Liu et al, 2019 ; Wu et al, 2021 ). The spike shapes (action potentials) were monitored and stored by Brain Ware (TDT 3, Tucker-Davis Technologies, United States) during recording.…”
Section: Methodsmentioning
confidence: 99%